(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The link between religion and politics is a historical relationship that has many sides ranging from influence and effectiveness to decline and marginalization. However, history has no civilization without religion, values, and traditions. The relationship between religion and international relations is one of the main topics raised in the intellectual and cultural scene. It is clear now that religion has moved from being absent and neglected to being a key player in interpreting current international relations. The current paper focuses on the religious dimension and its expected active role in current international relations, which are considered effective and impartial mediators to bring peace to the various conflict areas around the world. Moreover, the research sheds light on the attempt of the religious dimension to resolve current conflicts and existing crises between states and conflicting parties, leading to a peaceful political settlement, trying to defuse crises before they occur and prevent the causes of future conflicts, which will be reflected in global security, peace, and stability.